Analysis of Farmers' Income Differences Using The Cocoa-Patchouli Intercropping System And The Cocoa Monoculture System In Puduria Jaya Village Buke Sub District South Konawe District - Citra, Yuliana; Yunus, Lukman; Limi, Muhammad Aswar (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2021)
This study aims to determine the differences in farming income for the cropping system of the patchouli cacao intercropping system and the cocoa monoculture system in the Puduria Jaya Village Buke Sub District South Konawe District. This research was conducted in Puduria Jaya Village Buke Sub District, South Konawe District in 2019. The determination of research respondents was carried out by proportional stratified random sampling. Methods of data analysis using income analysis and t-test. The results showed that the average income of patchouli intercropping farmers was IDR 16,172,200 / ha and the income of cocoa monoculture farmers was IDR 3,904,783 / ha. The income of patchouli cocoa intercropping farmers and cocoa monocultures shows a significant difference where the income of patchouli cacao intercropping patterns is greater than that of cocoa monocultures.